Antiviral Activity of Carbon Dots: Strategies and Mechanisms of Action - Plinio Innocenzi; Davide De Forni; Franco Lori (Small Structures)
The COVID‐19 pandemic profoundly changes the perception of the impact of viral diseases on society and the consequent need to develop new and more effective technologies in vaccines and antivirals. Thus, research in the field of antivirals has received a new and strong impetus by considering new approaches and innovative methodologies. One example has been the numerous published studies on antiviral nanosystems developed from nanoparticles, among the most promising of which are carbon dots (C‐dots). C‐dots are effective antivirals due to multiple mechanisms of action. They are also, in general, water‐soluble and noncytotoxic. However, the data reported in the literature are still fragmented and cover different families of viruses and types of C‐dots. Therefore, a comparative study is needed to identify possible strategies for designing C‐dots with antiviral activity. This article aims to provide a comparative and critical analysis of the published data on C‐dots and their antiviral properties against various types of viruses. By exploring the relationship between the composition and properties of C‐dots, this article aims to shed light on the mechanism of their antiviral activity. The review has highlighted the potential of C‐dots as antiviral agents and would serve as a basis for further research in this field.